MITIGATION OF DISASTER RISK REDUCTION IN PANGANDARAN REGENCY - Pancasilawan, Ramadhan (Sosiohumaniora, 2020)
The government has a function to protect its people, including managing the disaster. The purpose of government in natural disaster management is a function that is expected to be carried out with full commitment. Disaster management is an activity carried out comprehensively, and there is a need for active stakeholder involvement. Pangandaran Regency is a disaster-prone area in West Java Province. This article aims to describe the mitigation launched by the Pangandaran Regency government to reduce disaster risk. The method used is qualitative, which uses observation data collection techniques, literature studies, and interviews with informants consisting of government and community elements. Pangandaran Regency has been stretched to get out of the tsunami disaster that had occurred. Even mitigation efforts have been carried out with the involvement of various stakeholders in the Pangandaran Regency. With mitigation, disaster risk reduction can be made. Therefore the government should make efforts to overcome disaster risk through the Mitigation Program by the Regional Disaster Management Agency (BPBD/Badan Penanggulanan Bencana Daerah). Disaster mitigation in Pangandaran Regency consists of two types: Mitigation with a Structural approach and Non-Structural approach. A structural approach is focusing on physical development, such as the construction of temporary evacuation sites or the construction of an early warning system (EAS). Non-structural mitigation carried out in the form of non-physical development, such as disaster education to school children and also to the community through activities carried out by mothers. Disaster training is given to private parties so that they can understand their role when disaster strikes.